Nota sobre la denominada responsabilidad contractual. ¿Falso mito o categoría histórica en constante transformación? - Espinoza Espinoza, Juan (Pontificia Universidad Católica del Perú, 2016)
In this article, the author explains the forms, consequences, and exceptions of breach of a contract from the perspective of comparative law. Thus, he aims to understand legal situations, which seek to protect the right of credit, such as the repair of the damages. The author makes distinctions when defining whether the security obligation is part of the contract or not, which allows to distinguish the nature of objectivity or subjective contractual liability.

En el presente artículo, el autor explica las formas, consecuencias y excepciones del incumplimiento de un contrato desde el derecho comparado. Así, pretende comprender las situaciones jurídicas, las cuales buscan tutelar el derecho de crédito, como el hecho de reparar el daño.El autor hace distinciones al momento de definir si la obligación de seguridad forma parte o no del contrato, permitiendo distinguir la naturaleza objetiva o subjetiva de la responsabilidad contractual.
Note on the denominated contractual liability. False myth or historical category in constant transformation?
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01